2006
DOI: 10.2533/000942906777674921
|View full text |Cite
|
Sign up to set email alerts
|

Switch-Peptides: From Conformational Studies to Alzheimer's Disease

Abstract: Studies on designed peptides that exhibit high tendencies for medium-induced conformational transitions have recently attracted much attention because structural changes are considered as molecular key processes in degenerative diseases. The experimental access to these events has been limited so far mainly due to the intrinsic tendency of the involved polypeptides for self-association and aggregation, e.g. amyloid β plaque formation, thought to be at the origin of Alzheimer's disease. We have developed a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2007
2007
2008
2008

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
0
18
0
2
Order By: Relevance
“…Furthermore, flexibility in the incorporation of multiple, orthogonally protected switch elements, which can be triggered in a selective and specific manner by using chemical, enzymatic, and/or photolytic procedures, [8][9][10] could open new possibilities in protein engineering and the design of "smart" materials with tunable structural, functional, and physiochemical properties.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, flexibility in the incorporation of multiple, orthogonally protected switch elements, which can be triggered in a selective and specific manner by using chemical, enzymatic, and/or photolytic procedures, [8][9][10] could open new possibilities in protein engineering and the design of "smart" materials with tunable structural, functional, and physiochemical properties.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the stability of bsheet-rich amyloid fibrils against proteases, acids, and chemical denaturants, increasing evidence from human [4] and in vitro studies indicates that a dynamic structure exists within amyloid fibrils and suggests that the process of amyloid formation is reversible. [5a,b] These findings, along with the fact that strategies aimed at the destabilization of amyloid fibrils and/or the acceleration of their clearance seem to reverse the disease phenotype, [6][7] suggest that a detailed understanding of the stability and dynamic behavior of amyloid fibrils is of critical importance to the development of therapeutic strategies for amyloid diseases.Our research group has previously shown [8][9][10] that the incorporation of molecular switches into polypeptides, based on an in situ intramolecular O!N acyl group migration, [11] allows for the controlled induction or reversal of secondary structural transitions [12a,b,c] and self-assembly of small peptide chains. Herein we describe a switch peptide that is designed to disrupt amyloid-like b-sheet assemblies through the controlled induced transition from a b-sheet to an a-helix structure (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…N acyl migration. [5][6][7][8][9][10][11][12][13][14][15][16] However, because of the special synthetic and purification skills required to prepare the full-length Ab switch-peptides, such peptides are not suitable for use in highthroughput screening assays. Therefore, the development of reliable model systems that are readily accessible and adaptable to automated HTS is of particular interest to understanding the mechanism of amyloid formation and facilitating the discovery of aggregation inhibitors of Ab and other amyloid-forming proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we [5][6][7][8] and others [9][10][11][12] have shown that various steps along the amyloid formation pathway, including peptide/ protein misfolding, self-assembly, and amyloid formation and disassembly, can be triggered in a highly controllable manner through the incorporation of molecular switches into the amyloid-forming polypeptides, based on in situ intramolecular O! N acyl migration.…”
Section: Introductionmentioning
confidence: 99%